Analysis of Daily Behavioral Patterns of Purebred Cats Before and After Sterilization - Henny Chandra; Sutrisnawati Sutrisnawati; Syech Zainal; Fatmah Dhafir; Masrianih Masrianih; Manap Trianto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Male domestic cats tend to exhibit different behaviors influenced by reproductive hormones, such as aggression, territorial instincts, and relatively high levels of exploratory activity. Sterilization (castration) has been shown to reduce the production of these hormones, which may consequently affect cats' daily behavioral patterns. This study aimed to examine changes in the daily behavior of domestic male cats before and after sterilization (castration). Observations were conducted on 15 cats (A–O), with variables including feeding frequency, sleeping patterns, grooming behavior, play activity, aggressive behavior, social interactions, and physical health. The method employed was direct observation of cat behavior before and after the sterilization procedure. The findings revealed significant behavioral changes following sterilization, including reduced aggression, decreased roaming activity, increased resting time, and more regular feeding patterns. In addition, social interactions with humans and other cats increased, while the cats’ physical condition became more stable. The degree of behavioral change varied among individual cats and was influenced by factors such as breed, age, individual temperament, and the environment in which they were kept. Therefore, sterilization not only plays an important role in population control but also contributes to improved behavioral stability and overall welfare in domestic male cats.